Post-transplant Lymphoproliferative Disorder Following Cardiac Transplantation - Asleh, Rabea; Alnsasra, Hilmi; Habermann, Thomas M.; Briasoulis, Alexandros; Kushwaha, Sudhir S. (Frontiers in Cardiovascular Medicine, 2022)
Post-transplant lymphoproliferative disorder (PTLD) is a spectrum of lymphoid conditions associated with the Epstein Barr Virus (EBV) and the use of potent immunosuppressive drugs after solid organ transplantation. PTLD remains a major cause of long-term morbidity and mortality following heart transplantation (HT). Epstein-Barr virus (EBV) is a key pathogenic driver in many PTLD cases. In the majority of PTLD cases, the proliferating immune cell is the B-cell, and the impaired T-cell immune surveillance against infected B cells in immunosuppressed transplant patients plays a key role in the pathogenesis of EBV-positive PTLD. Preventive screening strategies have been attempted for PTLDs including limited patient exposure to aggressive immunosuppressive regimens by tapering agents, anti-viral prophylaxis, routine EBV monitoring and avoidance of EBV seromismatch. Our group has also demonstrated that conversion from calcineurin inhibitor to the mammalian target of rapamycin (mTOR) inhibitor, sirolimus, as a primary immunosuppression was associated with a decreased risk of PTLD following HT. The main therapeutic measures consist of immunosuppression reduction, treatment with rituximab and use of immunochemotherapy regimens. The purpose of this article is to review the potential mechanisms underlying PTLD pathogenesis, discuss recent advances, and review potential therapeutic targets to decrease the burden of PTLD after HT.